Pergerakan Islam Indonesia Masa Jepang (1942-1945) - Alvin Noor Sahab Rizal (JURNAL INDO-ISLAMIKA, 2014)
The Japanese occupation period in Indonesia began in 1942 and ended on August 17, 1945. The entry of Japan into Indonesia brought broader changes for the Indonesian people, especially in education, which during the Dutch colonial period was discriminatory. Japan realizes that the majority of Indonesian people adheres Islam, at first this was not a problem, as evidenced by Japan's cooperation with Muslims in the early days of entering Indonesia. Japan established PETA (Defender of the Motherland) an institution consisting of Indonesians. In this organization Indonesians were educated and trained to hold arms, the Office of Religious Affairs (Shumubu), the Majlis Syuro Muslimin Indonesia, and Hezbollah were established. Although furthermore Japan must consider which of the Muslims could fulfill its colonial interests in Indonesia.